2006
DOI: 10.1175/jtech1867.1
|View full text |Cite
|
Sign up to set email alerts
|

Phased-Array Design for Biological Clutter Rejection: Simulation and Experimental Validation

Abstract: This paper highlights recent results obtained with the Turbulent Eddy Profiler (TEP), which was developed by the University of Massachusetts. This unique 915-MHz radar has up to 64 spatially separated receiving elements, each with an independent receiver. The calibrated raw data provided by this array could be processed using sophisticated imaging algorithms to resolve the horizontal structures within each range gate. After collecting all of the closely spaced horizontal slices, the TEP radar can produce three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
(30 reference statements)
0
28
0
Order By: Relevance
“…Because of the flexible and simultaneous beams provided through CRI, the TEP radar is ideal for the study of various DBS configurations with different pointing angles and numbers of beams. In addition, images of echo power and radial velocity across the region of across the DBS beams are obtained through the socalled pulse-pair beam-forming (PPB) process after successful phase calibration (Cheong et al 2004). The PPB is an efficient joint implementation of beam forming and the pulse-pair processor, which can be used to estimate the spectral moments without the need of synthesizing time series for each beam position.…”
Section: Experimental Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the flexible and simultaneous beams provided through CRI, the TEP radar is ideal for the study of various DBS configurations with different pointing angles and numbers of beams. In addition, images of echo power and radial velocity across the region of across the DBS beams are obtained through the socalled pulse-pair beam-forming (PPB) process after successful phase calibration (Cheong et al 2004). The PPB is an efficient joint implementation of beam forming and the pulse-pair processor, which can be used to estimate the spectral moments without the need of synthesizing time series for each beam position.…”
Section: Experimental Configurationmentioning
confidence: 99%
“…Coherent radar imaging (CRI) was developed to reconstruct a two-dimensional, angular distribution of the atmospheric structure within the volume illuminated by the transmitted beam (e.g., Kudeki and Sürücü 1991;Palmer et al 1998;Yu et al 2000;Hélal et al 2001). In addition, the angular distribution of radial velocity can be obtained by an efficient algorithm (Cheong et al 2004). CRI can be thought of as a beam-forming technique, in which a number of receiving beams can be synthesized simultaneously by coherently combining signals from spatially separated receivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using CRI, moving clutter is able to be suppressed. From the CRI measurement using TEP, Cheong et al (2006) succeeded in separating clear-air echoes and the biological scattering which was moving in the grating-lobe region, and demonstrated that the separation of biological scattering greatly reduced the error of wind velocity estimates. Chen et al (2007) also applied CRI to data measured by multiple antenna profiler radar (MAPR) of National Center for Atmospheric Research (NCAR) in order to mitigate effects of bird contamination in wind velocity estimates.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…It mostly affects L-band and UHF-systems, that is Boundary Layer profilers and Tropospheric profilers, as discussed in Wilczak et al (1995). Intermittent clutter is an issue for the standard Doppler-beam swinging radars as well as for spaced antenna and imaging radar systems, where new mitigation techniques like adaptive beamforming have recently been proposed (Cheong et al, 2006;Chen et al, 2007). We mention in passing that other remote sensing instruments used in Meteorology are also affected by migrating birds (Mastrantonio et al, 1999;Gauthreaux and Belser, 1998;Gauthreaux et al, 1998;Zhang et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%